FORMS, METHODS AND METHODS OF FORMING A SENSE OF NATIONAL PRIDE IN STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
A particular nation's position and place in the world community does not depend on its large number or small number. On the contrary, the ability to show national characteristics, the deep understanding of the rights of the representatives of the nation, not to be materially and morally dependent on other nations, and to exist independently determines its status in the international arena.